GENERAL MECHANISM OF FOLDING - Kuliyev G.G.; Buryakovskiy L.A.; Dzhevanshir R.D. (My University, 1989)
In this paper we present a mathematical model of a general mechanism of folding. We emphasize that in this formulation the nature of the forces producing the folding is immaterial. The rather general character of the model enables us to give these forces and other parameters specific geometric, mechanical, or mining geological interpretations of various kinds and to make a qualitative and quantitative analysis of the concrete results. Our approach uses the three-dimensional linearized theory of stability and differs from the earlier studies, which investigate stability only in the case of uniaxial compression, by taking fuller and more diverse account of the factors that produce loss of stability and of the boundary conditions (which are fundamental in stability problems) accompanying this process.